The Assessment of Infrasound and Low Frequency Noise Impact on the Results of Learning in Primary School – Case Study - ZAGUBIEŃ, Adam; WOLNIEWICZ, Katarzyna (Archives of Acoustics, 2020)
The aim of the research was to determine the occurrence of possible, significant levels of infrasound and low frequency noise both in classrooms and around the primary school. Two sources of noise during research were significant: traffic on the national road and a wind farm, located near the school building. So far, few studies have been published regarding the impact of low-frequency, environmental noise from communication routes. The identification of hazards in a form of estimated noise levels resulted in preliminary information whether the location of the school near the road with significant traffic and the nearby wind farm can cause nuisance to children. There have been determined the criteria for assessing infrasound and low frequency noise. There have been made third octave band analyses of noise spectrum and the essential noise indicators were calculated. The results of learning in that school were thoroughly analysed for a long period of time and they were compared to the results obtained in other schools within a radius of 200 km situated near similar noise sources. Chosen assessment criteria show small exposure to low frequency noise. Measured infrasound noise levels are below hearing threshold.